Modelling ecosystem response in the climate change era: the potential distribution of Natura 2000 priority habitat types in Greece under future climate scenarios - Alexandros D. Kouris; Athanasios S. Kallimanis; Panayotis Dimopoulos; Ioannis P. Kokkoris (Ecological Modelling, 2026)

The role of Earth observation in ecosystem accounting: A review of advances, challenges and future directions - Ioannis P. Kokkoris; Bruno Smets; Lars Hein; Giorgos Mallinis; Marcel Buchhorn; Stefano Balbi; Ján Černecký; Marc Paganini; Panayotis Dimopoulos (Ecosystem Services, 2024)

Ecosystem accounting for water resources at the catchment scale, a case study for the Peloponnisos, Greece - Eleni S. Bekri; Ioannis P. Kokkoris; Dimitrios Skuras; Lars Hein; Panayotis Dimopoulos (Ecosystem Services, 2024)

MAES implementation in Greece: Geodiversity - Giorgos Mallinis; Christos Domakinis; Ioannis P. Kokkoris; Stefanos Stefanidis; Panayotis Dimopoulos; Ioannis Mitsopoulos (Journal of Environmental Management, 2023)

Natura 2000 public awareness in EU: A prerequisite for successful conservation policy - Ioannis P. Kokkoris; Dimitrios Skuras; Yannis Maniatis; Panayotis Dimopoulos (Land Use Policy, 2023)

Definition and application of expert knowledge on vegetation pattern, phenology, and seasonality for habitat mapping, as exemplified in a Mediterranean coastal site - V. Tomaselli; M. Adamo; G. Veronico; S. Sciandrello; C. Tarantino; P. Dimopoulos; P. Medagli; H. Nagendra; P. Blonda (Plant Biosystems, 2017)

A novel method for assessing and mapping multiple impacts due to a technical construction project - Thomas M. Koutsos; Georgios C. Dimopoulos; Andreas P. Mamolos (Landscape and Ecological Engineering, 2016)

How does plant species composition change from year to year? A case study from the herbaceous layer of a submediterranean oak woodland - E. Chaideftou; A. Kallimanis; E. Bergmeier; P. Dimopoulos (Community Ecology, 2012)

Biogeographical determinants for total and endemic species richness in a continental archipelago - A. S. Kallimanis; E. Bergmeier; M. Panitsa; K. Georghiou; P. Delipetrou; P. Dimopoulos (Biodiversity and Conservation, 2010)

Riparian woodland flora in upland rivers of Western Greece - S. ZOGARIS; Y. CHATZINIKOLAOU; P. DIMOPOULOS (Mediterranean Marine Science, 2008)
Although natural riparian woodlands are an important feature that affects the quality of aquatic conditionsin streams and rivers, surveying riparian zone flora is rarely implemented in the Mediterraneancountries. We developed a rapid assessment method for gathering standardized plot-based woody flora andvegetation data from riparian woodlands. In 2005 we surveyed 218 streamside vegetation plots at 109 sitesin upland areas of four major rivers in mainland Greece (Alfios, Acheloos, Arachthos, and Aoos). Herewe describe the survey method and provide selected results from its initial implementation. The simplicityand effectiveness of this survey procedure supports the use of rapid site-based biodiversity surveys for riparianzones alongside aquatic status assessments.

Identifying plant communities of thermophilous deciduous forest in Greece: Species composition, distribution, ecology and syntaxonomy - E. Bergmeier; P. Dimopoulos (Plant Biosystems, 2008)

Antimicrobial susceptibility of multidrug-resistant Gram negative bacteria to fosfomycin - M. E. Falagas; M. D. Kanellopoulou; D. E. Karageorgopoulos; G. Dimopoulos; P. I. Rafailidis; N. D. Skarmoutsou; E. A. Papafrangas (European Journal of Clinical Microbiology & Infectious Diseases, 2008)